Traumeel S : the sportsman's answer to enhanched exercise performance and the overtraining syndrome? - Kruger, P.E. (Pieter Ernst) (University of Pretoria, 2013)
Dissertation (MA (Human Movement Sciences)--University of Pretoria, 2004.